1990
DOI: 10.1152/jappl.1990.68.2.586
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine responses to exercise after training with beta-adrenergic blockade

Abstract: Exercise training has been shown to decrease plasma norepinephrine (NE) and epinephrine (EPI) levels during absolute levels of submaximal exercise, which may reflect alterations in sympathetic tone as a result of training. To determine if beta-adrenergic blockade altered these changes in the plasma concentration of catecholamines with exercise conditioning, we studied the effects of beta-adrenergic blockade on NE and EPI at rest and during exercise in 24 healthy, male subjects after a 6-wk exercise training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Plasma CA levels may be useful for investigating the pharmacological effects of drugs at rest and during exercise (Dimsdale et al 1984;Collomp et al 1994;Graham and Spriet 1995;Jackman et al 1996), particularly in the assessment of drugs which have effects through actions on adrenoceptors (Dimsdale etal. 1984;Wolfel et al 1990). However, plasma CA levels have seldom been measured in pharmacological studies of the horse (Snow et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma CA levels may be useful for investigating the pharmacological effects of drugs at rest and during exercise (Dimsdale et al 1984;Collomp et al 1994;Graham and Spriet 1995;Jackman et al 1996), particularly in the assessment of drugs which have effects through actions on adrenoceptors (Dimsdale etal. 1984;Wolfel et al 1990). However, plasma CA levels have seldom been measured in pharmacological studies of the horse (Snow et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Both cross-sectional studies of trained and untrained subjects and longitudinal training studies have found that training either does not change or actually decreases the rate of appearance (Ra) of fatty acids into plasma during exercise performed at the same absolute intensity (Jansson & Kaijser, 1987;Martin et al 1993;Klein et al 1994;Horowitz & Klein, 2000a). Plasma catecholamine concentrations, which stimulate lipolysis of adipose tissue TG during exercise, are lower during exercise performed at the same absolute intensity before and after training (Wolfel et al 1990;Phillips et al 1996b;Friedlander et al 1998b) despite a training-induced increase in the capacity to secrete adrenaline (Kjaer & Galbo, 1988). In addition, training does not alter lipolytic sensitivity to adrenaline.…”
Section: Exercise Trainingmentioning
confidence: 99%